Hubungan Sikap Ibu dan Dukungan Keluarga dengan Kelengkapan Imunisasi Lanjutan pada Baduta di Puskesmas Amplas Kecamatan Medan Amplas Tahun 2022 - Nurmala Sianipar; Deby Cyntia Yun; Lidya Sinuhaji; Astaria Br Ginting (Pusat riset dan Inovasi Nasional, 2022)
Background: Many factors influence the completeness of basic immunization, such as parents, geographical location, vaccines, and health workers who provide immunization services. Even though the immunization program has been implemented well, there are still some immunization coverage that have not been achieved. Parents are the most important factor in scoring a child's complete immunization. Parents' participation in a health program is influenced by various factors and one of them is knowledge and attitudes towards the health program itself. Giving vaccines to children is the right way to anticipate the possibility of children being infected with diseases that are threatening at any time. Immunization functions to build a child's immunity against infectious diseases and dangerous diseases that can cause bodily defects. even death. Immunization given to children is the most effective way to protect children from tuberculosis (TB), diphtheria, pertussis (cocoon cough), tetanus (toothbrush). poliomyletis, measles, rubella and hepatitis B (Mai-imbi, 2021). During this time, parents had hepatitis B, meningitis, pneumonia and polio. VPD is a disease that is hoped to be eradicated or suppressed by implementing an immunization program Objective: Knowing the relationship between maternal attitudes and family support with the completeness of follow-up immunizations for young children at the Medan Amplas Community Health Center, Medan Amplas District in 2022. Method chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. Results: There is a relationship between the mother's attitude of family support and the completeness of advanced immunization for children in 2022. Suggestions are provided for research and for research sites and for educational institutions regarding perennial wound care.